BEZERRA DA SILVA E O CENÁRIO MUSICAL DE SUA ÉPOCA: ENTRE AS TRADIÇÕES DO SAMBA E A INDÚSTRIA CULTURAL (1970 2005) - SOUSA, Rainer Gonçalves (2009)
This work aims to establish a reading about the pathway of Bezerra da Silva from the artistic legacy that he left. Thereby, we promoted one revisit to the themes and questions inserted on the history of samba and we thought about the sambista s importance in the context of his time from the dialogue with his work. To rethink about the values of his production and the esteem of his contributions to the brazilian music, we appeal to the concepts of tradition and cultural industry, understood here as rich elements for us to explore the contrasts and the complexity of his artistic production.